Disintegration and Biodegradation in Soil of PBAT Mulch Films: Influence of the Stabilization Systems Based on Carbon Black/Hindered Amine Light Stabilizer and Carbon Black/Vitamin E - Souza, Patrícia Moraes Sinohara; Coelho, Felipe Mourão; Sommaggio, Lais Roberta Deroldo [UNESP]; Marin-Morales, Maria Aparecida [UNESP]; Morales, Ana Rita (Springer Nature, 2019)
This work characterized the disintegration and biodegradation of aged samples of PBAT films with and without photostabilization additives. The objective is to correlate these processes with properties affected after aging, i.e. molecular weight and gel content. Three different formulations were studied: pure polymer; PBAT with carbon black and hindered amine light stabilizer (HALS) and PBAT with carbon black and phenolic stabilizer vitamin E. The samples were monitored for 12 months. As expected, the lower level of photostabilization lead to the higher disintegration and biodegradation rates. Nevertheless, mineralization test showed that during time the differences among biodegradation rates become subtler. The crystallinity degree presented changes only at an advanced stage of degradation process, showing a reduction. The evaluation of the carbonyl index, molecular weight, surface morphology and visual analysis allowed to observe that the aged samples with lower gel content and lower molecular weight showed a faster degradation rate. The changes in material structure due to the increase of aromatic units concentration is the main hypothesis to explain the material behavior during degradation in soil.
Keywords: Biodegradation; Disintegration; Poly(butylene adipate co-terephthalate)